Scope and measurement of the effectiveness of primary patients’ care - Prusaczyk, Artur; Bogdan, Magdalena; Szafraniec-Buryło, Sylwia; Żuk, Paweł; Guzek, Marika; Oberska, Joanna (Journal of Education, Health and Sport, 2022)
Effectiveness of medical care is one of the most reliable parameters to assess individual aspects of the health care system. However, it should be emphasized that there is no unified definition of effectiveness in health care, on the basis of which these aspects can be assessed and compared. The aim of the study was to draw attention to the inability to make a reliable and authoritative assessment of effectiveness in health care due to the lack of a uniform definition and to emphasize their importance in the light of international comparative analysis. A review of the literature relating to the assessment of the quality and effectiveness of services provided by healthcare entities was performed. It has been defined that efficiency grows as the quality of healthcare increases and/or the cost of healthcare decreases, and effectiveness measurement should refer to a specific member of a medical stuff.